Proyeksi Penduduk Terhadap Kondisi Ketenagakerjaan Di Kota Kupang Dalam Menghadapi Bonus Demografi Tahun 2025 – 2030 - Hilario Taka Keor; Maria I. Hewe Tiwu; Fransina W. Ballo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to project the number and pyramid of population and employment conditions of Kupang City in facing the demographic bonus in 2025-2030. Population projection is done using the spectrum application and employment conditions are seen based on the availability and absorption of labor. The results showed that there was an increase in population in Kupang during 2025-2030 with a stationary population pyramid. The demographic bonus experienced by Kupang City has an impact on existing labor conditions, namely the availability of a potential workforce. However, unemployment remains a concern for the Kupang government. The existing business sectors in Kupang City in 2025-2030 are not able to keep up with the availability of labor, leading to high unemployment in 2025-2030.